Supervisors’ utterances in online supervision of first-year students’ dissertations - Augustsson, Gunnar; Jaldemark, Jimmy (Proceedings of the International Conference on Networked Learning, 2012)
While offline supervision is comprised of physical social clues, verbal communication, and drafts of texts, online supervision mainly focuses on written communication and electronic drafts. Participating in online supervision probably sets other requirements regarding clarity in the utterances of the supervisor. In online student supervision, it helps if supervisors are aware of differences in how their utterances of drafts are interpreted by students. Earlier research of supervision in online education has overlooked these differences in qualities of utterances. A problem that arises out of this omission is a deemphasizing of the quality in the social interplay between students and teachers in online supervision. A study of differences in written utterances of supervisors pays attention to this overlooking. As part of a greater research project of online supervision, the current study expands on earlier studies of the practice of online supervision by focusing on written utterances of supervisors and identifying and analysing differences in their comments on drafts of students’ dissertations. To fulfil this purpose online utterances’ of supervisors were analysed. Theoretical ideas of communication and online participation were used to interpret the empirical data. Overall we identify four categories of utterances: comments, points of view, instructions, and questions. The preliminary results of the research project implicate the importance of awareness among supervisors in online supervision, particularly on the nature of the utterances they make use of when supervising students’ academic writing. Such awareness makes it possible for supervisors to strategically emphasise students ’independence’. That could guide students through their writing by applying a balanced mix of comments, point of views, instructions, and questions. Reaching a balance in online supervisions may be very valuable in the process of supervising dissertation work. The preliminary results of the research project of online supervision suggest scrutinising how students perceive supervisor’s utterances of their drafts. That task will, together with an analysis of how supervisors perceive their own utterances, be examined more closely in further studies. Those studies could focus on how the dialogue between students and supervisors intersects in drafts of student’s dissertation.